Stress and displacement patterns during orthodontic intervention in the maxilla of patients with cleft palate analyzed by finite element analysis: a systematic review - Mikulewicz Marcin; Chojnacka Katarzyna (BMC, 2023)
Abstract Objective Rationale for the review in the context of what is already known about the evaluation of stress and displacement patterns using finite element analysis in the maxilla of patients with cleft palate after orthodontic intervention. Methods This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). The protocol for this systematic review was registered with PROSPERO (CRD42020177494). The following databases were screened: Medline (via PubMed), Scopus, Embase, and Web of Science. Results The search identified 31 records. 15 articles were retrieved for full texts and 11 of them were considered eligible for inclusion by 2 authors. Eventually, 11 articles were included in the qualitative analysis. Conclusions Finite element analysis is an appropriate tool for studying and predicting force application points for better controlled expansion in patients with UCLP.